The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1590/s0100-879x1997000400001
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine regulation of salt and water metabolism

Abstract: Neurons which release atrial natriuretic peptide (ANPergic neurons) have their cell bodies in the paraventricular nucleus and in a region extending rostrally and ventrally to the anteroventral third ventricular (AV3V) region with axons which project to the median eminence and neural lobe of the pituitary gland. These neurons act to inhibit water and salt intake by blocking the action of angiotensin II. They also act, after their release into hypophyseal portal vessels, to inhibit stressinduced ACTH release, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…The same authors also demonstrated that ANG II receptorcontaining neurons of the SFO project to the DRN (Tanaka et al 1998), which suggests that this pathway monitors circulating ANG II levels mediated by volume and/or sodium depletion. In summary, based on the above observations and evidence provided by Lind (1986), Johnson & Thunhorst (1997), McCann et al (1997), Fitch & Weiss (2000) and Franchini et al (2002), afferent information is conveyed to the NTS and from there to the DRN and ANG II-sensitive forebrain areas through pressure and/or volume receptors and renal sensors of tubular sodium load. At another level, increased circulating ANG II concentrations, reflecting body fluid volume and/or sodium depletion and a later increase in salt intake, are detected by the SFO, which conveys information to the DRN for the modulation of current sodium appetite.…”
Section: Figurementioning
confidence: 83%
“…The same authors also demonstrated that ANG II receptorcontaining neurons of the SFO project to the DRN (Tanaka et al 1998), which suggests that this pathway monitors circulating ANG II levels mediated by volume and/or sodium depletion. In summary, based on the above observations and evidence provided by Lind (1986), Johnson & Thunhorst (1997), McCann et al (1997), Fitch & Weiss (2000) and Franchini et al (2002), afferent information is conveyed to the NTS and from there to the DRN and ANG II-sensitive forebrain areas through pressure and/or volume receptors and renal sensors of tubular sodium load. At another level, increased circulating ANG II concentrations, reflecting body fluid volume and/or sodium depletion and a later increase in salt intake, are detected by the SFO, which conveys information to the DRN for the modulation of current sodium appetite.…”
Section: Figurementioning
confidence: 83%
“…CNS cholinergic stimulation contributed to the natriuretic effect, indicating the involvement of brain cholinergic system. Similarly, injection of carbachol into lateral ventricle, septal area, and preoptic region exerted the natriuresis and diuresis (Colombari et al 1992;McCann et al 1997).…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that many brain-specific natriuretic factors are located in periventricular structures related to water and salt balance control (3)(4)(5), demonstrating a possible link between insulin and natriuresis. Alternatively, we also cannot rule out the possibility that central NO-dependent neural pathways may control cholinergic, adrenergic or non-adrenergic non-cholinergic neurons and/or the hypothalamic/pituitary release of hormones, which in turn acutely modulates the action of insulin in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This observation has led to speculation that insulin may play a role in the development of increased blood pressure (1,2). On the other hand, the role of the central nervous system (CNS) in the control of blood pressure and hydroelectrolyte homeostasis has been demonstrated by several studies (3)(4)(5). Further studies of insulin action on neurons have demonstrated pleiotropic effects on ion flows (6), neurotransmitter uptake and release (7), cell growth, survival, and the transcriptional regulation of genes involved with differentiation (8), as well as possible modulation of several brain functions, such as food intake regulation, reproductive function and cardiovascular function (2,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%